2017
DOI: 10.1111/maps.12880
|View full text |Cite
|
Sign up to set email alerts
|

A new high‐precision40Ar/39Ar age for the Rochechouart impact structure: At least 5 Ma older than the Triassic–Jurassic boundary

Abstract: The Rochechourt impact structure in south‐central France, with maximum diameter of 40–50 km, has previously been dated to within 1% uncertainty of the Triassic–Jurassic boundary, at which time ~30% of global genera became extinct. To evaluate the temporal relationship between the impact and the Triassic–Jurassic boundary at high precision, we have re‐examined the structure's age using multicollector ARGUS‐V 40Ar/39Ar mass spectrometry. Results from four aliquots of impact melt are highly reproducible, and yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…3). This is consistent with several independent observations such as multiple levels with elevated Ir concentrations, lack of shocked minerals or spherules in the sediments, and lack of an impact structure of appropriate age and size 33,38,45,49,50 . This is also consistent with elevated Hg (and Hg/TOC) values reported for ETE sediments that have been interpreted as volcanic in origin 7,8,27 (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3). This is consistent with several independent observations such as multiple levels with elevated Ir concentrations, lack of shocked minerals or spherules in the sediments, and lack of an impact structure of appropriate age and size 33,38,45,49,50 . This is also consistent with elevated Hg (and Hg/TOC) values reported for ETE sediments that have been interpreted as volcanic in origin 7,8,27 (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Other explanations for the causes of mass extinction associated with the ETE include bolide impact [28][29][30] , or a combination of bolide impact and volcanism 31 that may have caused positive feed-back effects through destabilization of methane-hydrate reservoirs in the oceans and ocean acidification 16 . Two impact craters (Rochechouart, France 30 and Manicouagan, Canada 32 ) have previously been correlated to the end-Triassic but both have been shown to be older than ETE 33,34 . Soft-sediment deformation structures (seismites) in end-Triassic strata in the UK were originally suggested to have been impact-related 29 , but have also been mapped elsewhere across NW Europe and attributed to repeated seismicity connected to tectonic activity associated to CAMP emplacement 35,36 .…”
mentioning
confidence: 99%
“…Evidence for impact coinciding with the end-Triassic at *201 Ma is somewhat dubious (e.g., Olsen et al, 2002;Simms, 2003Simms, , 2007Tanner et al, 2004;Hesselbo et al, 2007;Kring et al, 2007;Schmieder et al, 2010b;Smith, 2011;Lindström et al, 2015), although earlier reports of putative shocked quartz grains at the Triassic/Jurassic boundary in Austria (Badjukov et al, 1987) and Italy (Bice et al, 1992) and an iridium anomaly (Olsen et al, 2002) certainly leave room for new research. The Latest Triassic (Rhaetian) *40 km-diameter Rochechouart impact structure in France previously had an age that overlapped with the Triassic/Jurassic boundary (Schmieder et al, 2010a), but new Ar-Ar results suggest that the impact occurred some *5 Myr before the transition (Cohen et al, 2017). Similar to widespread volcanism during the end-Permian, the Central Atlantic Magmatic Province (CAMP) may be a driving force of extensive seismicity, emission of gases, and extinction at the end of the Triassic (e.g., Marzoli et al, 1999;Lindström et al, 2015;Davies et al, 2017).…”
Section: The Role Of Impacts and Impact Ages In Earth's Biospherementioning
confidence: 99%
“…While the Ordovician period can be regarded as a time of intense impact flux, there is currently no evidence for synchronous multiple impact events resulting in the formation of larger-scale impact crater chains on Earth. Although such a scenario had been proposed for at least five impact structures with overlapping ages (Manicouagan and Lake Saint Martin in Canada, Red Wing Creek in the United States, Rochechouart in France, and Obolon in Ukraine) in the Late Triassic some 214 Myr ago (Spray et al, 1998), more recent Ar-Ar age determinations on the Lake Saint Martin (227.8 -0.9 Ma) (Schmieder et al, 2014a) and (Cohen et al, 2017;cf. Schmieder et al, 2010b) impacts and refined stratigraphic age constraints for Obolon (<185 Ma) (Schmieder and Buchner, 2008) demonstrated that all of those craters have very different ages and are thus unrelated.…”
Section: Geochronologic Evidence For Double and Multiple Impact Eventmentioning
confidence: 99%
“…Key Triassic Earth system events include the onset of the break up and northward drift of the supercontinent Pangea (Dietz and Holden, 1970;Robinson, 1973;Olsen, 1997;Olsen and Kent, 2000), frequent carbon cycle excursions, and major changes in pCO 2 levels (e.g., Payne et al, 2004;Berner, 2006;Whiteside et al, 2010;Hönisch et al, 2012;Schaller et al, 2015;Foster et al, 2017). During the Late Triassic, sudden paleoenvironmental events include reoccurring flood basalt volcanism such as the Wrangellia Large Igneous Province (Greene et al, 2010, and references within) and the Central Atlantic Magmatic Province (Whiteside et al, 2010;Schoene et al, 2010;Blackburn et al, 2013), as well as at least three hypervelocity impact events, the largest of which is the Manicouagan impact structure in Canada (Ramezani et al, 2005;Grieve, 2006;Schmieder et al, 2010Schmieder et al, , 2014Cohen et al, 2017). At the same time, the Late Triassic witnessed a number of important evolutionary events, such as the origin and early diversification of dinosaurs, lizards, mammaliaforms, and lissamphibians on land, and the diversification of scleractinian corals and calcareous nannoplankton in the ocean (e.g., Rogers et al, 1993;Stanley, 2003;Falkowski et al, 2004;Furin et al, 2006;Luo, 2007;Irmis, 2011;Fraser and Sues, 2011;Stocker et al, 2019).…”
Section: Introductionmentioning
confidence: 99%